2012
DOI: 10.1111/j.1525-1470.2012.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Concept in Youth with Congenital Facial Differences: Development and Recommendations for Medical Providers

Abstract: Congenital facial differences may impact a child's self-perception, activities and valuation, and what has been termed their "self-concept." This article reviews what constitutes self-concept, and its development during childhood and adolescence. The literature examining the role of physical appearance, specifically congenital facial differences on individuals' perceptions of self are reviewed in the context of psychosocial development. Positive self-concept can impact healthy behaviors, positive interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In this study, parents reported that their children’s self-perception of “being different” started to develop in conjunction with the eruption of primary teeth and before or approaching three years of age. This finding supports the growing evidence from children’s developmental psychology that self-perceptions starts to develop as early as two to three years of age [26,30,31,32].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, parents reported that their children’s self-perception of “being different” started to develop in conjunction with the eruption of primary teeth and before or approaching three years of age. This finding supports the growing evidence from children’s developmental psychology that self-perceptions starts to develop as early as two to three years of age [26,30,31,32].…”
Section: Discussionsupporting
confidence: 88%
“…It may be because the teacher has to deal with dozens of students and has limited time and energy to take care of every student in the class. Contemporary adolescents commonly lack self-confidence due to their over-ambitious pursuits, resulting in a lower positive self-concept [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Marden et al [1964] defined a major anomaly as having "an adverse effect on either the function or social acceptability of the individual" and a minor anomaly as one that is "neither of medical nor cosmetic consequence to the patient." The self-image and social acceptability of individuals with morphologic anomalies are complex psychological and social issues [Marik and Hoag, 2012;Masnari et al, 2012], which should be distinguished from the medical or biological description of the anomaly. Given the enormous variation in social and personal attitudes toward physical differences, we were hesitant to include such concepts in our definitions.…”
Section: Anomaly Morphologicmentioning
confidence: 99%